Art Therapy: Media Pendidikan Kreatif untuk Menanggulangi Remaja dengan Gangguan Kecemasan - Alif Sukma Muclisin; Cindy Wahyuningsih; Indar Sabri; Setyo Yanuartuti; Djuli Djatiprambudi (Journal of Education on Social Science (JESS), 2023)
Anxiety disorders often appear in adolescents aged 10-24 years. When adolescents experience anxiety disorders the accompanying emotional reactions are body tension, fear, distress, and anxiety in response to certain situations that are perceived as threatening. Anxiety in adolescents can be measured by the Hamilton Rating Scale For Anxiety (HRS-A), and the Child Anxiety subscale of the Revised Children's Manifest Anxiety Scale (RCMAS), as well as graphical tests, such as Draw A Person (DAP), Draw a Tree (BAUM), and House Tree Person (HTP), which are performed by the adolescent (subject). The purpose of this study is to address adolescents with anxiety disorders. This study uses qualitative methods to describe anxiety disorders in adolescents and quantitative methods to see the effect of art therapy as a creative education media in overcoming anxiety disorders in adolescents. The subjects in this study were 5 adolescents with anxiety disorders of which 2 subjects were given art therapy. The sampling technique used purposive sampling method. The results of this study, art therapy has been shown to be able to reduce anxiety in adolescents with anxiety disorders. From the results of the above research, it can be concluded that art therapy will produce positive developments at different levels.